Climate change adaptation relevance of Tanzania's national budget and its level of devolution - Noah M. Pauline (Danish Institute for International Studies (DIIS), 2023)
In Tanzania, climate change adaptation is financed by international development assistance and by nationally generated revenue. While international development assistance is registered by OECD and climate change adaptation relevance tagged by donors, the proportion of the nationally generated revenue that is climate change adaptation relevant is unknown. This paper analyses the climate change adaptation relevance of the national budget (from 2014 to 2022), using the same methodology applied in a previous study (Yanda et al., 2013). The study further assesses the degree to which climate change adaptation financed is devolved to local government. The study finds that a disproportionately high proportion of climate adaptation finance is used at central government levels due to priorities being established at the ministry level. Moreover, the study finds that local governments lack discretion over climate change adaptation finance due to the country's highly centralised policies, practices and procedures. Qualitative fieldwork indicates that nearly all climate change adaptation finance accessed by local governments comes with a central government tag (directive) on how to use it.
Keywords: 330; climate change adaptation; Tanzania